Exploring the nexus between sports performance and genetics: a comprehensive literature review: Sports and genetics - Kahya, Sedat; Taheri, Morteza (Cellular and Molecular Biology, 2024)
Sport is a multifactorial phenomenon that is influenced by many factors. Although many factors affect sports performance, genetic factors may be important issues that need to be examined. In addition, the relationship between sports performance and genes is still unclear. Due to the developments in omics technologies, approximately 185 genetic markers have been identified for the relationship between sports performance and genes. These genes are expressed differently in metabolism according to the characteristics of sports performance. The aim of this study was to investigate the relationship between sports and genetics. Pubmed, Pubmed Central and Google Scholar internet search engines were used in current study. Additionally, the PRISMA technique was used in the study design. For this purpose, COL1A1, COL5A1, ACTN3 and ELN genes may be important regulators on soft tissues. For endurance sports, genes like ACE, ACTN3, ADRB2, HFE, COL5A1, BDKRB2, NOS3, HIF, VEGF, AMPD and PPARGC1A significantly may influence performance limits. ACE and ACTN3 genes, on the other hand, may determine power/strength and speed skills in athletes. As a result, knowing the athlete’s genetic predisposition to sports can be effective in achieving success.